Determinants of drug survival for etanercept in a long‐term daily practice cohort of patients with psoriasis. (18th February 2014) - van den Reek, J.M.P.A.; van Lümig, P.P.M.; Driessen, R.J.B.; van de Kerkhof, P.C.M.; Seyger, M.M.B.; Kievit, W.; de Jong, E.M.G.J.
Abstract : What's already known about this topic? Etanercept has proven to be effective and well tolerated in patients with psoriasis in several randomized controlled trials. What does this study add? This is the first daily practice study calculating drug survival rates of patients treated with etanercept for a maximum observation period of 7·5 years. Determinants of longer drug survival were calculated for general drug survival, and separately for discontinuation due to adverse events or ineffectiveness of therapy. Summary: Background: Long‐term data of etanercept drug survival in patients with psoriasis in daily practice are scarce. Objectives: The primary objective was to describe drug survival for etanercept in a long‐term daily practice cohort of patients with psoriasis. The secondary objective was to identify determinants of drug survival for etanercept in general and separately for discontinuation due to adverse events or ineffectiveness of therapy. Methods: Data were extracted from a prospective daily practice cohort of patients treated with biologics for psoriasis. Drug survival was analysed by Kaplan–Meier survival curves and split for two reasons for discontinuation: adverse events and ineffectiveness. Determinants of drug survival were analysed using univariate Cox regression analysis and multivariate Cox regression analysis with backward selection. Results: We included 193 patients (512 patient‐years treated) with a maximum treatment duration of 7·5 years. The overall drug survival rates were 77%, 41% and 30% after 1, 4 and 7·5 years, respectively. The mean survival duration was 3·8 years (95% confidence interval 3·4–4·3). Reasons for discontinuation were ineffectiveness (33·7%), adverse events (11·9%), both ineffectiveness and adverse events (4·7%) or other reasons (e.g. pregnancy planned) (5·7%). Determinants related to longer general drug survival were male sex [hazard ratio (HR) 0·55], prior anti‐tumour necrosis factor (TNF)‐α use (HR 0·57) and lower etanercept dose (HR 0·65). Younger age (HR 0·83), lower body mass index (HR 0·63) and lower etanercept dose (HR 0·71) were related to a decreased risk of discontinuation due to side‐effects. A lower mean weekly dose of etanercept (HR 0·63) was related to a decreased risk of discontinuation due to ineffectiveness of therapy. Conclusions: We present the longest analysis of drug survival for etanercept in psoriasis to date. Determinants of longer overall etanercept drug survival were male sex, prior anti‐TNF therapy and lower etanercept dose. The determinants of longer drug survival depended on the reason for discontinuation of etanercept.